Colocial Expression of Students of SMA Negeri 4 Ambon in Oral Language (Ethnographic Study of Communication) - Carolina Sasabone; Petrus. J. Pattiasina; Merlin Rutumalessy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Language is seen as a science, cannot be separated in interaction between humans and is translated into the scope of education, both formal, non-formal and informal. In social interaction, language functions to convey messages in interaction or conversation. Language is seen from an axiological point of view, then language is a form of human behavior in the dimensions of social life of society which naturally grows and develops in various aspects of human life, especially the association of students in the school environment. In connection with this research, the problem discussed is "colloquial expressions of students at SMA Negeri 4 Ambon in the ethnographic perspective of communication". This research is a descriptive qualitative research, namely synchronous language research. This is in line with Mahsun's opinion (2017: 86) which states that synchronous language research is language research that is carried out by observing the phenomenon of a language at a certain time, and is descriptive. The focus is a comprehensive description or describe and explain the data obtained. The research data is in the form of utterances in the conversations of SMA Negeri 4 Ambon students. Speech that contains colloquial expressions. The results of this study found that the students' colloquial expressions were in the form of questions, statements and orders. While the colloquial expression functions found are assertive functions, directive functions, expressive functions and commissive functions.